CAROTENOID-ENRICHED DIET FOR PRE-MATURATION STAGE OF POND-REARED TIGER SHRIMP, Penaeus monodon PART I. THE EFFECTS ON GROWTH, PIGMENTATION AND WHOLE BODY NUTRIENT CONTENT - Asda Laining; Ike Trismawanti; Kamaruddin Kamaruddin; Makmur Makmur (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2017)
Carotenoids, besides as a natural pigment, may have vital roles in the growth of crustacean. The aim of this study was to clarify the influence of combined carotenoids given since pre-maturation stage on the growth performances, pigmentation and biochemical composition of the whole body of pond-reared tiger shrimp, Penaeus monodon. Two experimental diets were supplemented with or without carotenoid mixture consisting of astaxanthin, canthaxanthin and other carotenoids contained in Spirulina. The carotenoid mixture was supplemented in the commercial diet normally used as a starter feed for tiger shrimp, re-pelleted and fed to tiger shrimp with an initial body weight of 31.7±1.3 g. Shrimp were stocked in four 1,000 m2 concrete ponds with a density of 1 shrimp/m2 and fed until the shrimp reached maturation stage (broodstock size). Variables observed were growth performances and pigmentation properties during the pre-maturation stage and total carotenoid content in several tissues of the female broodstock after being fed with the diets until maturation stage. After 16 weeks, shrimp fed with carotenoid-enriched diet (PC) diet produced significantly (P<0.05) higher biomass than the diet without the enrichment (PO). The color of raw shrimp fed with PC diet was darker with greenish-brown compared to shrimp fed PO diet which was greenish blue. The visual appearances of 3-min steamed shrimp produced the color of red-orange for shrimp fed carotenoid compared to orange-yellow for control PO. The total carotenoid content in the whole body of shrimp fed PC diet were significantly (P<0.05) enhanced compared to control PO diet which was 42.8 ±5.8 and 55.8± 5.1 µg/g for PO and PC diet, respectively. Supplemental carotenoid in the pre-maturation diet increased the biomass production from 23.1±1.9 kg to 30.2 ±0.1 kg and enhanced the color of the shrimp which was in line with carotenoid content in the whole body of pond-reared tiger shrimp.